Biological control: a major component for the longterm cowpea pest management strategy - Tamò, Manuele; Srinivasan, R.; Dannou, E.A.; Agboton, C.; Datinon, B.; Dabiré, C.; Baoua, I.; Ba, Malick N.; Haruna, B.; Pittendrigh, Barry Robert (International Institute of Tropical Agriculture, 2012)
Current strategies to control insect pest problems in cowpea include, on the preventive side, host plant resistance and conservation biological control. Because very often these management options alone cannot provide adequate control, curative measures need to be taken, which include augmentative and inundative biological control, the application of biopesticides, and the judicious use of synthetic pesticides. Using synthetic pesticides as the first line of defense against insect pests is not considered a sustainable component of a long-term management strategy for various reasons, but mainly because of human and environmental health considerations. Hence, the development of biological-control-based interventions becomes an attractive and essential activity in cowpea pest management. Using the case studies of flower thrips and pod borers, we illustrate how biological control is developed and deployed. Each example starts with biodiversity studies to explore potential biological control candidates, and continues with the development of efficient rearing methodologies, combined with delivery systems. Irrespective of the target organism, whether a local or exotic parasitoid, or a biopesticide, each natural enemy needs to have its own deployment strategy. Thereby, apart from obvious ecological considerations determining the suitability of a particular biological control agent, one of the most critical factors for a successful biocontrol project is the development of efficient and simple delivery systems. In the case of classical biological control, this ought to be less important because the natural enemy was expected to spread by itself, so there is usually no need for interventions beyond inoculative releases. However, in some cases the use of an improved, semi-artificial inoculation system proved to be instrumental for successful establishment. The development of a robust system for rearing and deploying natural enemies, if possible with full participation of farming communities, becomes even more crucial for augmentative/inundative biological control.